Comparing the predictive value of screening to the use of electronic health record data for detecting future suicidal thoughts and behavior in an urban pediatric emergency department: A preliminary analysis. Issue 6 (13th September 2021) - Haroz, Emily E.; Kitchen, Christopher; Nestadt, Paul S.; Wilcox, Holly C.; DeVylder, Jordan E.; Kharrazi, Hadi
Abstract: Aim: Brief screening and predictive modeling have garnered attention for utility at identifying individuals at risk of suicide. Although previous research has investigated these methods, little is known about how these methods compare against each other or work in combination in the pediatric population. Methods: Patients were aged 8–18 years old who presented from January 1, 2017, to June 30, 2019, to a Pediatric Emergency Department (PED). All patients were screened with the Ask Suicide Questionnaire (ASQ) as part of a universal screening approach. For all models, we used 5‐fold cross‐validation. We compared four models: Model 1 only included the ASQ; Model 2 included the ASQ and EHR data gathered at the time of ED visit (EHR data); Model 3 only included EHR data; and Model 4 included EHR data and a single item from the ASQ that asked about a lifetime history of suicide attempt. The main outcome was subsequent PED visit with suicide‐related presenting problem within a 3‐month follow‐up period. Results: Of the N  = 13, 420 individuals, n  = 141 had a subsequent suicide‐related PED visit. Approximately 63% identified as Black. Results showed that a model based only on EHR data (Model 3) had an area under the curve (AUC) of 0.775 compared to the ASQ alone (Model 1), which had an AUC of 0.754. Combining screening and EHR data (Model 4) resulted in a 17.4% (absolute difference = 3.6%) improvement in sensitivity and 13.4% increase in AUC (absolute difference = 6.6%) compared to screening alone (Model 1). Conclusion: Our findings show that predictive modeling based on EHR data is helpful either in the absence or as an addition to brief suicide screening. This is the first study to compare brief suicide screening to EHR‐based predictive modeling and adds to our understanding of how best to identify youth at risk of suicidal thoughts and behaviors in clinical care settings.